Silicon-based optoelectronic integrated circuit for label-free bio/chemical sensor - Song, Junfeng (2013)
We demonstrate a silicon-based optoelectronic integrated circuit (OEIC) for label-free bio/chemical sensing application. Such on-chip OEIC sensor system consists of optical grating couplers for vertical light coupling into silicon waveguides, a thermal-tunable microring as a tunable filter, an exposed microring as an optical label-free sensor, and a Ge photodetector for a direct electrical readout. Different from the conventional wavelength-scanning method, we adopt low-cost broadband ASE light source, together with the on-chip tunable filter to generate sliced light source. The effective refractive index change of the sensing microring induced by the sensing target is traced by scanning the supplied electrical power applied onto the tracing microring, and the detected electrical signal is read out by the Ge photodetector. For bulk refractive index sensing, we demonstrate using such OEIC sensing system with a sensitivity of ~15 mW/RIU and a detection limit of 3.9 μ-RIU, while for surface sensing of biotin-streptavidin, we obtain a surface mass sensitivity of Sm = ~192 µW/ng·mm−2 and a surface detection limit of 0.3 pg/mm2. The presented OEIC sensing system is suitable for point-of-care applications.